Relationship of Organizational Culture and Leadership Style on Performance of Z Generation in Startup Company on SBM ITB (Journal of Innovation, Business and Entrepreneurship, 2020)
Culture is regularly reenacted and generated by our experiences with others. Formed value of others, we think of that as